Simultaneous estimation of gallic acid, quercetin and kaempferol from euphorbia prostrata W. Ait by high performance thin layer chromatography - KAMINI DONDE; APEKSHA SHINDE (International Journal of Pharma and Bio Sciences, 2017)
A sensitive and reliable quantitative High Performance Thin Layer Chromatographic (HPTLC) method have been developed for the quantitation of Gallic acid, Quercetin and Kaempferol from whole plant powder of Euphorbia prostrata W. Ait. which has antidiabetic activity. Methanolic extract of the whole plant powder of Euphorbia prostrata W. Ait. used for carrying out thin layer chromatography (TLC) on silica gel 60 F254 plates. Detection and quantitation was performed by using deuterium lamp at λ = 254 nm. Accuracy of the developed HPTLC method was checked by conducting the recovery study. The average percent content of Gallic acid, Quercetin and Kaempferol in whole plant powder of the used plant as estimated by the proposed method was found to be 0.3939mg/g, 0.1197 mg/g, and 0.2421mg/g respectively. The HPTLC method developed for the quantitative determination of Gallic acid Quercetin and Kaempferol from the whole plant powder of Euphorbia prostrata W. Ait. is rapid, simple and precise.